Deficiency of the Purinergic Receptor 2X7 Attenuates Nonalcoholic Steatohepatitis Induced by High-Fat Diet: Possible Role of the NLRP3 Inflammasome. (15th November 2017) - Blasetti Fantauzzi, Claudia; Menini, Stefano; Iacobini, Carla; Rossi, Chiara; Santini, Eleonora; Solini, Anna; Pugliese, Giuseppe
Abstract : Molecular mechanisms driving transition from simple steatosis to nonalcoholic steatohepatitis (NASH), a critical step in the progression of nonalcoholic fatty liver disease (NAFLD) to cirrhosis, are poorly defined. This study aimed at investigating the role of the purinergic receptor 2X7 (PR2X7 ), through the NLRP3 inflammasome, in the development of NASH. To this end, mice knockout for the Pr2x7 gene ( Pr2x7 −/− ) and coeval wild-type (WT) mice were fed a high-fat diet (HFD) or normal-fat diet for 16 weeks. NAFLD grade and stage were lower in Pr2x7 −/− than WT mice, and only 1/7 Pr2x7 −/− animals showed evidence of NASH, as compared with 4/7 WT mice. Molecular markers of inflammation, oxidative stress, and fibrosis were markedly increased in WT-HFD mice, whereas no or significantly reduced increments were detected in Pr2x7 −/− animals, which showed also decreased modulation of genes of lipid metabolism. Deletion of Pr2x7 gene was associated with blunted or abolished activation of NLRP3 inflammasome and expression of its components, which were induced in liver sinusoidal endothelial cells challenged with appropriate stimuli. These data show that Pr2x7 gene deletion protects mice from HFD-induced NASH, possibly through blunted activation of NLRP3 inflammasome, suggesting that PR2X7 and NLRP3 may represent novel therapeutic targets.